"I Felt Close to Death": A Phenomenological Study of Female Strangulation Survivors of Intimate Terrorism. Issue 4 (2nd October 2017) - Vella, Sylvia A.; Miller, Marianne M.; Lambert, Jessica E.; Morgan, Martha L.
ABSTRACT: This qualitative study focused on the lived experiences of female survivors of severe intimate partner violence that involved strangulation. Such domination manifests via power and control tactics, which include extremely violent behavior. Existing literature on domestic violence is extensive; however, previous researchers have not addressed the psychological complexities of strangulation survivors' lived experiences, especially from a feminist perspective. To address this gap, the researchers used transcendental phenomenology. The primary investigator analyzed interview transcripts and revealed two core themes of strangulation survivors: "Betrayal and violence altered view of self and others" and "Fear of death, fear in daily life."